2023
DOI: 10.3390/plants12173077
|View full text |Cite
|
Sign up to set email alerts
|

Back to Nature: Medicinal Plants as Promising Sources for Antibacterial Drugs in the Post-Antibiotic Era

Emad M. Abdallah,
Bader Y. Alhatlani,
Ralciane de Paula Menezes
et al.

Abstract: Undoubtedly, the advent of antibiotics in the 19th century had a substantial impact, increasing human life expectancy. However, a multitude of scientific investigations now indicate that we are currently experiencing a phase known as the post-antibiotic era. There is a genuine concern that we might regress to a time before antibiotics and confront widespread outbreaks of severe epidemic diseases, particularly those caused by bacterial infections. These investigations have demonstrated that epidemics thrive und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 172 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…Several studies have demonstrated that thyme, Astragalus, tangerine peel, and dandelion have antioxidant and immune-promoting effects ( 38–40 ) and partially growth-promoting effects ( 24 ). Furthermore, the intricate and variability of the synergistic potential of plant extract combinations ( 41 ) may be a contributing factor to the lack of improvement in broiler growth performance in this experiment. The strain specificity of the host’s immune and gut health response to probiotics ( 42 ) may also be a contributing factor to the non-significant differences in growth performance in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that thyme, Astragalus, tangerine peel, and dandelion have antioxidant and immune-promoting effects ( 38–40 ) and partially growth-promoting effects ( 24 ). Furthermore, the intricate and variability of the synergistic potential of plant extract combinations ( 41 ) may be a contributing factor to the lack of improvement in broiler growth performance in this experiment. The strain specificity of the host’s immune and gut health response to probiotics ( 42 ) may also be a contributing factor to the non-significant differences in growth performance in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived sources present an alternative reservoir of bioactive compounds with potential applications of therapeutic or prophylactic agents against various diseases [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. To date, 350,000 vascular plant species are known, and new species are discovered yearly [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in efficiency and rising concern regarding the application of synthetic substances, mainly related to antibiotic-resistant bacteria, have awoken the interest among research groups to investigate and utilize MAPs as substitutes. A synthetic substance is usually composed of a single main bioactive compound, while MAPs’ essential oils or extracts provide a wider range of bioactive compounds with a synergism mechanism against the application target [ 11 ].…”
Section: Introductionmentioning
confidence: 99%